Unique potential of immature adult-born neurons for the remodeling of CA3 spatial maps - Mugnaini, Matías (2022)
Mammalian hippocampal circuits undergo extensive remodeling through adult neurogenesis. While this process has been widely studied, the specific contribution of adultborn granule cells (aGCs) to spatial operations in the hippocampus remains unknown. Here we show that optogenetic activation of 4-week-old (young) aGCs in free-foraging mice produces a non-reversible reconfiguration of spatial maps in proximal CA3, while rarely evoking neural activity. Stimulation of the same neuronal cohort on subsequent days recruits CA3 neurons with increased efficacy but fails to induce further remapping. In contrast, stimulation of 8-week-old (mature) aGCs can reliably activate CA3 cells but produce no alterations in spatial maps. Our results reveal a unique role of young aGCs inremodeling CA3 representations, a potential that can be depleated and is lost withmaturation. This ability could contribute to generate orthogonalized downstream codes supporting pattern separation.